A Facile One‐Pot Route for the General Synthesis of Triazole Linked Chiral 2‐Substituted Benzimidazoles. (18th May 2013) - Dutta, Samrat; Sarkar, Swarbhanu; Sen, Asish Kumar
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>